A reverse genetics and genomics approach to gene paralog function and disease: myokymia and the juxtaparanode - Marafi, Dana; Kozar, Nina; Duan, Ruizhi; Bradley, Stephen; Yokochi, Kenji; Al Mutairi, Fuad; Saadi, Nebal Waill; Whalen, Sandra; Brunet, Theresa; Kotzaeridou, Urania; Choukair, Daniela; Keren, Boris; et al. (The American journal of human genetics, 2022)
The leucine-rich glioma-inactivated (LGI) family consists of four highly conserved paralogous genes, LGI1-4, that are highly expressed in mammalian central and/or peripheral nervous systems. LGI1 antibodies are detected in subjects with autoimmune limbic encephalitis and peripheral nerve hyperexcitability syndromes (PNHSs) such as Isaacs and Morvan syndromes. Pathogenic variations of LGI1 and LGI4 are associated with neurological disorders as disease traits including familial temporal lobe epilepsy and neurogenic arthrogryposis multiplex congenita 1 with myelin defects, respectively. No human disease has been reported associated with either LGI2 or LGI3. We implemented exome sequencing and family-based genomics to identify individuals with deleterious variants in LGI3 and utilized GeneMatcher to connect practitioners and researchers worldwide to investigate the clinical and electrophysiological phenotype in affected subjects. We also generated Lgi3-null mice and performed peripheral nerve dissection and immunohistochemistry to examine the juxtaparanode LGI3 microarchitecture. As a result, we identified 16 individuals from eight unrelated families with loss-of-function (LoF) bi-allelic variants in LGI3. Deep phenotypic characterization showed LGI3 LoF causes a potentially clinically recognizable PNHS trait characterized by global developmental delay, intellectual disability, distal deformities with diminished reflexes, visible facial myokymia, and distinctive electromyographic features suggestive of motor nerve instability. Lgi3-null mice showed reduced and mis-localized Kv1 channel complexes in myelinated peripheral axons. Our data demonstrate bi-allelic LoF variants in LGI3 cause a clinically distinguishable disease trait of PNHS, most likely caused by disturbed Kv1 channel distribution in the absence of LGI3.
Gesehen am 13.02.2023